2021
DOI: 10.1016/j.jsps.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Organization factors influencing nurse ability to prevent and detect adverse drug events in public hospitals using a patient safety model

Abstract: The objective of this study was to measure organization factors that can influence the ability of nursing staff to prevent and detect ADEs in public hospitals using Systems Engineering Initiative for Patient Safety (SEIPS) model. Methods This was a multi-center cross-sectional study. The study included a self-administered paper-based survey which was distributed and collected between October through December 2019. The study participants were nurses from 11 public hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…One of the positive findings was that most nurses can (83.6%) report the ADEs. This is comparable to a previous study finding which found that nurses had an effective role in reporting ADEs [31]. The applied CSM was based on Swanson's caring theory [25].…”
Section: Resultssupporting
confidence: 82%
“…One of the positive findings was that most nurses can (83.6%) report the ADEs. This is comparable to a previous study finding which found that nurses had an effective role in reporting ADEs [31]. The applied CSM was based on Swanson's caring theory [25].…”
Section: Resultssupporting
confidence: 82%